2018
DOI: 10.1115/1.4041275
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency Measurement of Temperature and Composition Spots With LITGS

Abstract: Temperature and composition spots in a turbulent flow are detected and time-resolved using Laser Induced Thermal Grating Spectroscopy (LITGS). A 355 nm wavelength PIV laser is operated at 0.5 -1 kHz to generate the thermal grating using biacetyl as an absorber in trace amounts. In a open laminar jet, a feasibility study shows that small ( 3%) fluctuations in the mean flow properties are well captured with LITGS. However, corrections of the mean flow properties by the presence of the trace biacetyl are necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Simulations from Rodrigues, Busseti & Hochgreb (2020) and experiments from De Domenico et al. (2019 b ) show that the injected plume mixes sufficiently very close to the injection location, allowing for a quasi-one-dimensional approximation. Following the analysis of Broadwell & Breidenthal (1984), it can be demonstrated that the full mixing penetration occurs before the spot enters the nozzle.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Simulations from Rodrigues, Busseti & Hochgreb (2020) and experiments from De Domenico et al. (2019 b ) show that the injected plume mixes sufficiently very close to the injection location, allowing for a quasi-one-dimensional approximation. Following the analysis of Broadwell & Breidenthal (1984), it can be demonstrated that the full mixing penetration occurs before the spot enters the nozzle.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Wang et al 2019;Yoon 2020), with their contribution to the instabilities (e.g. Eckstein & Sattelmayer 2006;Schulz et al 2019) and with their measurements (Wassmer et al 2017;De Domenico et al 2019). Most of the modelling efforts to date have been about entropy-wave dispersion in fully developed turbulent duct flows (Sattelmayer 2002;Morgans, Goh & Dahan 2013;Morgans & Duran 2016;Giusti et al 2017;Fattahi, Hosseinalipour & Karimi 2017;Christodoulou et al 2020;Hosseinalipour et al 2020), where shear dispersion was identified as the dominant mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…2017; De Domenico et al. 2019). Most of the modelling efforts to date have been about entropy-wave dispersion in fully developed turbulent duct flows (Sattelmayer 2002; Morgans, Goh & Dahan 2013; Morgans & Duran 2016; Giusti et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, there is no systematic investigation focused on the decay of compositional waves. Existing studies of compositional noise have speculated rather differently about the evolution of these waves [22,[57][58][59] and a conclusive view is yet to emerge. The current work aims to address this issue through conduction of high fidelity numerical simulations of the propagation process of a compositional wave in turbulent channel flows.…”
Section: Nomenclaturementioning
confidence: 99%